1998
DOI: 10.1002/(sici)1096-9071(199804)54:4<243::aid-jmv2>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hepatitis B, hepatitis C, and GB virus C/hepatitis G virus infections in liver disease patients and inhabitants in Ho Chi Minh, Vietnam

Abstract: The prevalence of hepatitis B virus (HBV), hepatitis C virus (HCV), and GB virus C or hepatitis G virus (GBV-C/HGV) infections was determined in 289 patients with liver disease in Ho Chi Minh City and 890 healthy inhabitants of its rural area, Dalat City, Vietnam, respectively. Serum HCV RNA and GBV-C/HGV RNA were detected by reverse transcription-polymerase chain reaction (RT-PCR). HBsAg, HCV antibodies, and GBV-C/HGV RNA were detected in 139 (47%), 69 (23%), and ten (3%) subjects, respectively, often accompa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 31 publications
3
43
0
Order By: Relevance
“…Moreover, 34.8% to 80% of patients with liver cancer can be attributable to HBV. 8,9,11,17,27,41 For the association between HCV and liver cancer, there are very limited data and only 1 study has reported that 14% of liver cancer was due to HCV infection. 17 Mathematical models estimate nationally that by 2013, the number of people with chronic HBV infection will reach its peak at 8.6 million cases and then decrease to 8 million by 2025, as a direct impact of the universal infant vaccination.…”
Section: Burden Of Viral Hepatitis and Liver Diseasessupporting
confidence: 89%
See 4 more Smart Citations
“…Moreover, 34.8% to 80% of patients with liver cancer can be attributable to HBV. 8,9,11,17,27,41 For the association between HCV and liver cancer, there are very limited data and only 1 study has reported that 14% of liver cancer was due to HCV infection. 17 Mathematical models estimate nationally that by 2013, the number of people with chronic HBV infection will reach its peak at 8.6 million cases and then decrease to 8 million by 2025, as a direct impact of the universal infant vaccination.…”
Section: Burden Of Viral Hepatitis and Liver Diseasessupporting
confidence: 89%
“…22 The HBsAg prevalence among the subpopulations was also reported by various studies in Vietnam. The HBsAg prevalence ranged from 8.1% to 17.6% among health care workers and was also high among blood donors, people with liver diseases, people who inject drugs (PWIDs) and female sex workers ([FSWs]; Tables 1 and 2) 22,9,11,23,6,18,14 The available data suggest that hepatitis B virus (HBV) is a major cause of liver disease and liver cancer in Vietnam. Between 30.1% and 87.6% of liver cirrhosis cases and 34.8% and 80% of hepatocellular carcinoma can be attributed to HBV infection.…”
Section: Overview-hepatitis B and C And Hiv Coinfection In Vietnammentioning
confidence: 97%
See 3 more Smart Citations